Retaining individualities: the photodynamics of self-ordering porphyrin assemblies. Issue 9 (18th December 2015) - Quan, Wen-Dong; Pitto-Barry, Anaïs; Baker, Lewis A.; Stulz, Eugen; Napier, Richard; O'Reilly, Rachel K.; Stavros, Vasilios G.
Abstract : Retained photochemical properties – a simple porphyrin–polyDMA conjugate with the ability to self assemble into large (∼1 μm) vesicles in water. The photodynamics are remarkably preserved despite the extensive aggregation. Abstract : The retention of photochemical properties of individual chromophores is a key feature of biological light harvesting complexes. This is achieved despite extensive aggregation of the chromophores, which in synthetic chromophore assemblies often yields a change in spectral characteristics. As an alternative approach towards mimicking biological light harvesting complexes, we report the synthesis of porphyrin assemblies which retained the photochemical properties of the individual chromophore units despite their substantial aggregation. These new materials highlight a new bottom-up approach towards the design and understanding of more complex biomimetic and naturally occurring biological systems.